Synthesis, characterization, TDDFT calculation and biological activity of tetradentate ligand based square pyramidal Cu(ii) complexes1. Issue 83 (9th September 2015) - Bhunia, Apurba; Manna, Soumen; Mistri, Soumen; Paul, Aparup; Manne, Rajesh Kumar; Santra, Manas Kumar; Bertolasi, Valerio; Chandra Manna, Subal
<x xml:space="preserve">Abstract</x> Fluorescent Cu(ii) compounds have been synthesized, and characterized by structure analyses and DFT/TD-DFT calculations. Compounds show catecholase and anticancer activities.